Systematic Review of the Balloon Analogue Risk Task (BART) in Alcohol Research. - Canning, Jessica R; Schallert, Macey R; Larimer, Mary E (Alcohol & Alcoholism, 2022)
Risk-taking propensity has been crucial to the investigation of alcohol use and consequences. One measure, the balloon analogue risk task (BART), has been used consistently over the past two decades. However, it is unclear how this measure is related to alcohol outcomes. This paper systematically reviews the literature on the BART and alcohol outcomes. First, direct associations between the BART and alcohol use are reviewed including correlations, group comparisons, the BART's prediction of alcohol outcomes and BART performance after consuming alcohol. Then, potential moderators that explain when and for whom the BART is related to alcohol outcomes are reviewed. Finally, potential mechanisms that explain how the BART and alcohol outcomes are related are reviewed. This review reveals patterns in the BART suggesting risk-taking propensity may be related to changes in alcohol use over time; however, there is little evidence to suggest BART scores increase after consuming alcohol. Yet, additional research suggests adjusted average pump scores may be too simplistic for the amount of information the BART captures and understanding individual's patterns of responses on the BART is important for investigating its relation to alcohol outcomes. Finally, this review opens up several future directions for research to understand how risk-taking propensity is related to alcohol outcomes.